Association of CT thorax findings with galactomannan and aspergillus-specific polymerase chain reaction for diagnosis of invasive aspergillosis in patient with febrile neutropenia - Idris, Nurul Ain Mat (2018)
Background: The Computed Tomography (CT) features of Invasive Pulmonary Aspergillosis (IPA) include Airway and Angio Invasive type. However those features are nonspecific and diagnosis should be made in conjunction with EORTC-MSG criteria. In this study, we evaluated the association between the CT findings and Galactomannan and Aspergillus specific PCR in patient with febrile neutropenia. Methods: Patients with hematological malignancy who had persistent febrile neutropenia of 3 days or more despite of antibiotic underwent CT thorax within 2 weeks of clinical diagnosis of IPA. Blood serum for Galactomannan assay and Aspergillus specific PCR were performed. Changes of CT thorax were documented and association between mycological findings were analyzed using Fisher exact test. Significant association taken at p value of < 0.05. Results: A total of 26 patients were enrolled in our study. CT findings were positive in 17(65.4%), 8(30.8%) was positive for Galactomannan and 9(34.6%) for PCR. There was significant association between PCR and CT thorax finding (p value 0.009, 95% CI) but not between Galactomannan and CT Thorax (p value 0.667, 95% CI). Conclusion: Combination of PCR and CT thorax can be used as a non-invasive tools for early diagnosis of IPA. The Aspergillus specific PCR might to be consider as one of the mycological criteria in EORTC-MSG for diagnosis of IPA in the future.